2015
DOI: 10.1175/jamc-d-13-0210.1
|View full text |Cite
|
Sign up to set email alerts
|

A Field Experiment on the Small-Scale Variability of Rainfall Based on a Network of Micro Rain Radars and Rain Gauges

Abstract: Small-scale summer rainfall variability in a semiarid zone was studied by deploying five vertically pointing Micro Rain Radars (MRRs) along a nearly straight line and by using 12 rain gauges in the study area of the Xilin River catchment in China. The spatial scales of 4 and 9 km correspond to the resolution of precipitation radar and rainfall products from satellites. The dataset of the MRRs and rain gauges covers two months in the summer of 2009. Three parameters, that is, spatial correlation, intermittency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Earlier studies have shown the usefulness of such analysis in gauge-satellite comparisons, hydrological and meteorological modeling and setting up gauge networks (Habib et al, 2001;Krajewski et al, 2003;Ciach and Krajewski, 2006;Villarini et al, 2008;Liechti et al, 2012;Luini and Capsoni, 2012;Mandapaka and Qin, 2013;Li et al, 2014;Chen et al, 2015). Spearman correlation coefficients have been computed between each pair of rain gauge locations for different rain accumulation periods.…”
Section: Spatial Correlationmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies have shown the usefulness of such analysis in gauge-satellite comparisons, hydrological and meteorological modeling and setting up gauge networks (Habib et al, 2001;Krajewski et al, 2003;Ciach and Krajewski, 2006;Villarini et al, 2008;Liechti et al, 2012;Luini and Capsoni, 2012;Mandapaka and Qin, 2013;Li et al, 2014;Chen et al, 2015). Spearman correlation coefficients have been computed between each pair of rain gauge locations for different rain accumulation periods.…”
Section: Spatial Correlationmentioning
confidence: 99%
“…6 (a for the SWM and b for the NEM). The spatial correlation distance is obtained by fitting a modified exponential model on the data samples in correlograms (intergauge correlation coefficient vs. intergauge distance), as given by Ciach and Krajewski (2006),…”
Section: Spatial Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, rainfall monitoring by ground-level rain gauges is considered the most reliable measurement system for hydrologic applications because it physically captures pluvial water. In hydrologic engineering and research, rain gauge measurements frequently serve as reference data for evaluation of indirect or remote sensing rainfall systems such as weather radars and satellites (Krajewski and Smith 2002;Seo and Breidenbach 2002;Habib 2012;Price 2014;Chen 2015;Fencl 2015). However, limitations must be considered since a single rain gauge is a point measurement with limited direct information defining spatial variation of rainfall across an area.…”
Section: Introductionmentioning
confidence: 99%